Family Suicide Bombing: A Psychological Analysis of Contemporary Terrorism - Rindha Widyaningsih; K Kuntarto (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
Terrorist organizations are now transforming into small cells and spreading their ideology to various parts of the world. The acts of terrorism in the Surabaya bomb case provide a new paradigm of the involvement of family members or an inner circle in their actions. The involvement of family members is considerably related to some psychological aspects. This study aims to provide a psychological analysis of suicide bombing terrors involving family members. The data obtained were analyzed using the perspective of Moghaddam’s theory, ‘staircases to terrorism’. The result indicates that the suicide bomber who has brought their family members in the action has gone through these six stages of psychological aspects: (1) Search for meaning. Actors seeking self and social meaning and finding reasons from the radical ideology adopted; (2) Presenting the ideology. The idea arises to fight those who are considered to do injustice, and the desire to change the system of government and politics is legitimate; (3) Cultivation stage. The process of ideology processing justification for resistance to those who are considered to be doing injustices; (4) Control over members. The stages of correct or wrong assessment based on the fatwa of the leader; (5) Moral engagement. The stage of identity confirmation and the process of polarization of groups of friends and opponents; (6) Recruitment, which is the stage of active involvement in acts of terrorism ranging from planning, targeting, techniques used, time and location of targets to implementing recruitment.